The Requirements of Initiating a Mangosteen Supply Chain Management in Banyuwangi District, Indonesia - Astuti, Retno; Effendi, Mas’ud; ., Sucipto; ., Wignyanto (KnE Life Sciences, 2016)
In order to have competitive advantages, a supply chain management in Mangosteen business should be initiated in Banyuwangi Distric, East Java Indonesia. The aim of this research was to identify the requirements of initiating a Mangosteen supply chain management in Banyuwangi District and analyze the relationships between the requirements. Interpretative Structural Modeling was used to describe the relationships between the requirements of the chain. The availability of capital was the priority requirements to be fulfilled in initiating a Mangosteen supply chain management in Banyuwangi District. Keywords: Interpretative Structural Modeling, Mangosteen, Supply Chain Management.